Thinking About Religious Texts Anthropologically - Joel S. Kahn (Center for Research and Development of Religious Literature and Heritage, 2015)
This paper addresses the conference themes by asking what contribution anthropology can make to the study of religious literature and heritage. In particular I will discuss ways in which anthropologists engage with religious texts. The paper begins with an assessment of what is probably the dominant approach to religious texts in mainstream anthropology and sociology, namely avoiding them and focussing instead on the religious ‘practices’ of ‘ordinary believers’. Arguing that this tendency to neglect the study of texts is ill-advised, the paper looks at the reasons why anthropologists need to engage with contemporary religious texts, particularly in their studies of/in the modern Muslim world. Drawing on the insights of anthropologist of religion Joel Robbins into what he called the “awkward relationship” between anthropology and theology, the paper proposes three possible ways in which anthropology might engage with religious literature. Based on a reading of three rather different modern texts on or about Islam, the strengths and weaknesses of each of the three modes of anthropological engagement is assessed and a case is made for Robbins’s third approach on the grounds that it offers a way out of the impasse in which mainstream anthropology of religion finds itself, caught as it is between the ‘emic’ and the ‘etic’, i.e. between ontologically different worlds.